Non-Penal Countermeasures Efforts in Supporter Conflict (Study on PSIM vs Persis Conflict) - Laras Astuti; Nyoman Serikat Putra Jaya; R.B Sularto (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
The conflict between PSIM Yogyakarta and PERSIS Solo supporters is a conflict that has been going on for a long time. These conflicts often cause casualties and damage to public facilities. Severe sanctions do not frighten supporters and a deterrent to take anarchic actions. To overcome this, preventive efforts (non-penal) can be used as an alternative in resolving supporter conflicts. Through socio-legal research, this paper aims to find out more about non-penal countermeasures based on an analysis of the factors that cause supporter conflict. The results of the study, it is known that non-penal countermeasures can be done by emphasizing the efforts of the supporter development process as part of the criminal politics of prevention without punishment. The coaching process is based on three factors that cause supporting conflicts, namely based on the nature, position of the actors, and diversity of society. The police and supporter also have a strategic role in preventing criminal acts to minimize the occurrence of clashes between supporters. These roles include providing security personnel, conducting sweeping, and coordinating between related parties.